ADMINISTRATORS' ASSESSMENT OF THE PROVISIONS OF COOPERATIVE EDUCATION FOR SUCCESS OF AGRICULTURAL COOPERATIVE BUSINESS OWNERS IN ANAMBRA STATE (NAU Journal of Technology and Vocational Education, 2024)
The provision of cooperative education, without doubt, is a major determinant for the successof agricultural cooperative business especially in developing countries like Nigeria, wherecooperatives are used as a strategy in the development process. This study is aimed atassessing the provision of cooperative education among agricultural cooperative businessowners for success of their business in Anambra State. 50 cooperative administrators werepurposively sampled from the Management Committees of Agricultural Cooperative Businessand District Cooperative Officers (DCO's) in the twenty one local government areas ofAnambra State for the study. Two research questions guided the study. Data were collectedwith structured questionnaire which was analyzed using percentages and mean scores. Thefindings of the study revealed low provision of cooperative education by the government andthe cooperatives themselves. The findings also revealed bare provisions by non-governmentaland international bodies. It was recommended among others that government and nongovernmental bodies that provide financial support to agricultural cooperative business inNigeria should set aside some percentage of the funds provided for education of thecooperative members. This is to ensure effective use of such funds